Seafood safety and quality - Bari, Md. Latiful; Yamazaki, Kōji, 1961- (CRC Press/Taylor and Francis Group, 2018)
Seafood Safety and Quality continues to be a major public health issue and its importance has escalated to unprecedented levels in recent years. In this book, major seafood borne diseases and key safety issues are reviewed. In addition, emerging microbial agents, fish toxins and other contaminants including heavy metal; allergy, water safety and related topics are discussed. It also addresses the challenges faced by both developed and developing countries to ensure seafood safety in new seafood products and processing technologies, seafood trade, safety of foods derived from biotechnology, microbiological risks, emergence of new and antibioticresistant pathogens, particularly from emerging pathogens, directing research to areas of high-risk, focus intervention and establishment of target risk levels and target diseases or pathogens. The book serves as a comprehensive resource on the seafood borne diseases and a wide variety of responsible etiologic agents, including bacteria, viruses, parasites, seafood toxins, and environmental toxins. It has been written in a simple manner and should promote the efforts of the scientific community to deliver safe seafood for a better health and environment.
"A Science Publishers book."
Keywords: Seafood -- Microbiology.; Seafood industry -- Safety measures.; Seafood -- Contamination.; Foodborne diseases.; elektronické knihy; electronic books